Elementary teachers' use of content knowledge to evaluate students' thinking in the life sciences. Issue 7 (2nd May 2016) - Sabel, Jaime L.; Forbes, Cory T.; Flynn, Leslie
ABSTRACT: Science learning environments should provide opportunities for students to make sense of and enhance their understanding of disciplinary concepts. Teachers can support students' sense-making by engaging and responding to their ideas through high-leverage instructional practices such as formative assessment (FA). However, past research has shown that teachers may not understand FA, how to implement it, or have sufficient content knowledge to use it effectively. Few studies have investigated how teachers gather information to evaluate students' ideas or how content knowledge factors into those decisions, particularly within the life science discipline. We designed a study embedded in a multi-year professional development program that supported elementary teachers' development of disciplinary knowledge and FA practices within science instruction. Study findings illustrate how elementary teachers' life science content knowledge influences their evaluation of students' ideas. Teachers with higher levels of life science content knowledge more effectively evaluated students' ideas than teachers with lower levels of content knowledge. Teachers with higher content exam scores discussed both content and student understanding to a greater extent, and their analyses of students' ideas were more scientifically accurate compared to teachers with lower scores. These findings contribute to theory and practice around science teacher education, professional development, and curriculum development.